Upregulation of CD32 in T cells from infants with severe respiratory syncytial virus disease: A new costimulatory pathway? - Sananez, Inés (2020)
Respiratory syncytial virus (RSV) causes 33.1 million episodes of acute lower respiratory infections, resulting in about 3.2 million hospital admissions, and 59 600 in-hospital deaths in children younger than 5 years during 2015, mostly in developing countries. An RSV-neutralizing monoclonal antibody (mAb), palivizumab, has been used prophylactically for 20 years for infants born prematurely or with heart malformations. The RSV vaccine candidates are evaluated based on their induction of RSV neutralizing Abs. However, antibodies can also influence the outcome of diseases by activating effector functions through the receptors for the Fc portion of IgG (FcRs). Whether T cell express FcRs is still controversial, but recent studies strongly suggest that a minor fraction of T cells expresses FcRII (CD32). Moreover, it should be noted that most severe RSV cases occur in infected infants under the age of 6 months, who are born with relatively high amounts of maternal IgG Ab to RSV. We here show that severe RSV infection in infants is associated with a marked upregulation of CD32 on T cells, whose ligation promotes the activation of CD4+ and CD8+ T cells of hospitalized infants. These findings also suggest that during severe RSV infection in infants, the immune complexes might provide a stimulatory signal able to promote the activation of T cells contributing to the resolution of infection.